Pengaruh Celebrity Endorsement terhadap Purchase Decission dengan Brand Image sebagai Mediator pada Scarlett Whitening - Zulham Muji; Hedi Cupiadi; Dani Adiatma (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study was designed to examine Brand Image as an intervening variable in Purchase Decisions for Scarlett Whitening products influenced by Celebrity Endorsement. The background of this study shows that the development of digital technology has encouraged the massive use of celebrity endorsements in marketing strategies, but there is a gap in understanding regarding their effectiveness in shaping brand image and influencing purchasing decisions. This study adopts a quantitative approach using descriptive and causal methods. Primary data were collected through a questionnaire distributed to 96 respondents who are users of Scarlett Whitening, selected using the Lemeshow formula. The study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) using the SmartPLS software. Based on the research, Celebrity Endorsement has a very strong positive influence on Brand Image, and Brand Image has a positive influence on Purchase Decision. Additionally, Celebrity Endorsement also influences Purchase Decision directly and indirectly through Brand Image as an intervening variable. These findings demonstrate the importance of building a strong brand image through celebrity endorsement strategies to enhance consumer Purchase Decision.